2019
DOI: 10.1590/fst.12318
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of zinc in the agronomic biofortification of arugula

Abstract: Zinc deficiency affects one third of the population and a possible solution is the agronomic biofortification of vegetables. Due to the increased consumption of arugula, this vegetable has good potential of use; however, there are few researches on the subject. The objective of this study was to evaluate the effect of foliar zinc applications, at different times, on physiological, yield, nutritional, and biofortification parameters of the 'Broad Leaf ' arugula. Three doses (0.5, 1, and 1.5 kg ha-1 Zn) were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…These data corroborate with data obtained by Reyes et al (2019), who applied zinc in a single dose via arugula leaf for biofortification, despite observing phytotoxic effects on plants between 1 to 1.5 kg ha -1 did not show a decrease in productivity. The values found in the current experiment are close to the values found by other authors (Silveira et al, 2015;Vargas et al, 2017).…”
Section: Agronomic Traits Of Curly Lettuce Submitted To Zinc Biofortificationsupporting
confidence: 91%
See 1 more Smart Citation
“…These data corroborate with data obtained by Reyes et al (2019), who applied zinc in a single dose via arugula leaf for biofortification, despite observing phytotoxic effects on plants between 1 to 1.5 kg ha -1 did not show a decrease in productivity. The values found in the current experiment are close to the values found by other authors (Silveira et al, 2015;Vargas et al, 2017).…”
Section: Agronomic Traits Of Curly Lettuce Submitted To Zinc Biofortificationsupporting
confidence: 91%
“…Seema et al (2017), in a study with spinach, also observed that leaf zinc content increased as there was an increase in zinc content applied to the soil. According to Reyes et al (2019), foliar fertilization with up to 1.5 kg ha -1 of zinc, even when applied in soils with high micronutrient content, does not affect the physiological parameters and biomass of arugula.…”
Section: /9mentioning
confidence: 99%
“…After applying 22.7 kg ha −1 of Zn (in the form of Zn sulphate, ZnSO 4 ·7H 2 O) to the soil, Mao et al [ 90 ] observed a significant increase in the Zn concentration of the edible portions of canola ( Brassica napus L.) and cabbage ( Brassica rapa L. Chinensis Group) (by 25% and 200%, respectively). Zinc biofortification through foliar spray has been successfully performed in arugula ( Eruca sativa L.) using 1.5 kg ha −1 of ZnSO 4 ·7H 2 O, with a resulting +94% increase of leaf Zn concentration [ 91 ]. Among non-Brassicas leafy vegetables, in a study conducted by Barrameda-Medina et al [ 92 ] hydroponically cultured plants of lettuce ( Lactuca sativa L.) supplemented with 100 µM ZnSO 4 ·7H 2 O in the nutrient solution showed a 251% increase in leaf Zn concentration.…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…Arugula has been employed as a research plant in studies, including the recent ones that aimed to investigate light color and intensity on the plant's growth (Johnson et al, 2020) to understand selenium tolerance of the species (Santiago et al, 2020), and to increase yield through foliar zinc (Rugeles-Reyes et al, 2019), sulfur, and tyrosine treatments (Al-Mohammad and Al-Taey, 2019). However, the studies explaining the effects of chitosan treatment on Eruca vesicaria ssp.…”
Section: Discussionmentioning
confidence: 99%